Mental illness as social product or social construct: a contradiction in feminists’ arguments? - Busfield, Joan (Sociology of Health & Illness, 2008)
Feminists have been taken to task for suggesting both that the higher level of mental illness observed in women is a consequence of the oppression they face - an oppression which drives them into madness and mental disorder - and also that the concept of mental illness is a social construct inappropriately and incorrectly applied to women by a patriarchal order as a means of social control. This paper examines this supposed contradiction and the ideas that underly the contrasting contentions. It argues that the two positions are not in fact incompatible.
Number: 4
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; angleterre; approches et analyses; cours; discipline; europe; inégalités; patriarcat; premier cycle; périodes historiques; régions géographiques; santé; santé mentale; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; états-unis

Démédicaliser les corps, politiser les identités : convergences des luttes féministes et intersexes - Kraus, Cynthia; Perrin, Céline; Rey, Séverine; Gosselin, Lucie; Guillot, Vincent (Nouvelles Questions Féministes, 2008)
Number: 1
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; belgique; capacitisme; corps; cours; discipline; discours dominant; europe; france; féminisme interdisciplinaire; féminisme matérialiste; hétérosexisme; identités LGBTQIA2+; intersexuation; inégalités; luxembourg; marginalisation; militance; médecine; philosophie; premier cycle; psychiatrie; périodes historiques; queer; régions géographiques; santé; sciences; sciences humaines; soc2014; soc2051; sociologie; systèmes d'oppressions; thématiques; transféminisme; violences; violences médicales

Butch/Femme differences in substance use and abuse among young lesbian and bisexual women: Examination and potential explanations. - Rosario, Margaret; Schrimshaw, Eric W; Hunter, Joyce (Substance use & misuse, 2008)
The current study examined the role of gender atypical self-presentation on the alcohol, tobacco, and marijuana use, as well as symptoms of substance abuse/misuse, of an ethnically diverse sample of 76 young (ages 14-21 years) lesbian and bisexual women who were interviewed between 1993 and 1995 in New York City. Even after controlling for age, sexual identity, and social desirability, young butch women reported drinking alcohol more frequently and in greater quantity, smoking more cigarettes, and using marijuana more frequently than young femme women. Experiences of gay-related stressful events, internalized homophobia, and emotional distress were found to largely account for the butch/femme differences in tobacco and marijuana use, but not in higher levels of alcohol use. Despite the small convenience sample, these findings suggest that intervention efforts to address the higher levels of substance use among young lesbian and bisexual women may increase effectiveness by also addressing experiences of gay-related stress and emotional distress of young butch women. The study's limitations are noted
Keywords: 1900-1999; 1990-1999; amériques; identités LGBTQIA2+; personnes bisexuelles; personnes lesbiennes; périodes historiques; ressource en ligne; régions géographiques; santé; thématiques; états-unis